Features of organbation of independent nark of students from general art disciplines in the system of preparation of designers (Pedagogy of Higher and Secondary Education, 2009)
A study from general art disciplines is the important continent of high-quality trade education of future specialists of designer type. The pedagogical of organization of independent work of students of artistic specialities are probed. The ways of increase of officiency of study from general art disciplines are reflected due to organization of effective work of students.
Keywords: independent work of students; pedagogical terms of organization of independent work; effective independent work of students